2020
DOI: 10.1007/s00167-020-06293-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-based examination of the medial ligament complex shows gender- and age-related differences in laxity

Abstract: Purpose Ultrasound (US) examination of the medial joint space of the knee has played a subordinate diagnostic role up till now. The purpose of the present study was to describe mean values of medial joint width and to investigate the impact of gender, age, and body mass index (BMI) on medial joint laxity in healthy knees using modern, dynamic US in a standardized fashion in unloaded and standardized loaded conditions. Methods A total of 65 subjects with 79 healthy knees were enrolled in this study. All volun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Despite this variability, the trend of increasing medial joint space opening remains highly correlated to the grade of MCL lesion ultimately diagnosed. Furthermore, concomitant lesions of other stabilizing knee ligaments such as the anterior cruciate ligament magnifies the amount of medial joint space opening and clinical instability present (Table 4) [26,30,37,[42][43][44]52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this variability, the trend of increasing medial joint space opening remains highly correlated to the grade of MCL lesion ultimately diagnosed. Furthermore, concomitant lesions of other stabilizing knee ligaments such as the anterior cruciate ligament magnifies the amount of medial joint space opening and clinical instability present (Table 4) [26,30,37,[42][43][44]52].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, patients with an isolated MCL lesion had a smaller maximal medial gapping of 18 mm compared to patients with a combined injury of the MCL and one or both cruciate ligaments that allowed [30] dynamic MRI Clinical examination with valgus stress Gap width measurement: distance between medial tibial margin and the cortex of the medial femoral condyles Grade I rupture: 2.3 mm Grade II rupture: 2.9 mm (1.9-4.9 mm) a medial gapping as great as 29 mm [26,37]. Comparative analyses in healthy knees under valgus stress showed that a medial gapping of 3-11 mm can occur, even in the absence of medial joint pathology [44].…”
Section: Medial Gappingmentioning
confidence: 99%
“…Fifth, our method of image post-processing relies on time-consuming manual segmentations and, thus, is not (yet) ready for clinical implementation that would require automated segmentations and analyses for expedited workflows. Sixth, because of limited sample size we did not consider (statistically) the body donors' sex which may be a confounder as women tend to have lower medial joint space widths [16,43] and more severe valguslaxity [50][51][52]. Seventh, direct clinical translation of our approach is not readily possible.…”
Section: Discussionmentioning
confidence: 99%
“…Stress sonography has been under decade-long clinical investigation [15]. Despite its operator-dependence and reliance on high-resolution equipment, stress sonography is a promising and useful diagnostic tool if used properly and adopted by more joint surgeons and radiologists [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The medial tibiofemoral distance was defined by measuring the distance between the articular margins of the medial femoral condyle and the medial tibial plateau (Fig 3). 19…”
Section: Portable Ultrasound Techniquementioning
confidence: 99%